What future for history dependence in spatial economics? - Lin, Jeffrey; Rauch, Ferdinand (Regional science and urban economics, 2022)
History (sometimes) matters for the location and sizes of cities and neighborhood segregation patterns within cities. Together with evidence on rapid neighborhood change and self-fulfilling expectations, this implies that nature might not completely determine the spatial structure of the economy. Instead, the spatial economy might be characterized by multiple equilibria or multiple steady-state equilibrium paths, where history and expectations can play decisive roles. Better evidence on the conditions under which history matters can help improve theory and policy analysis.
Gesehen am 21.03.2023